Questionnaire-Based Survey Regarding the Rational Usage of Antimicrobial Agents in Food-Producing Animals in Romania - Ionela Popa; Kalman Imre; Adriana Morar; Ionica Iancu; Vlad Iorgoni; Timea Bochiș; Călin Pop; Alexandru Gligor; Tiana Florea; Sebastian Alexandru Popa; Viorel Herman; Ileana Nichita (Veterinary Sciences)
The annual rise in antimicrobial resistance (AMR) is a major public health concern. This Romanian questionnaire-based survey aimed to evaluate the appropriateness of routine antimicrobial use by veterinary practitioners in food-producing animals and to gauge their concerns about AMR. To gather data, an online questionnaire with 28 questions was developed and distributed nationwide to veterinarians via the Google Drive network and Google Forms. Despite this increased awareness, deviations in antimicrobial administration persist, often due to insufficient knowledge about AMR and the mechanisms of antimicrobial action. This study underscores the urgent need for prudent antimicrobial use in livestock production in Romania.